Towards a typology of internationalisation at home activities in academic disciplines: a study conducted at a Dutch university of applied sciences - Bulnes, Claudia; de Louw, Eveke (Compare, 2024)
Increasingly, internationalisation at home and internationalisation of the curriculum are adopted by universities across the globe but their systemic implementation is a complex process. For instance, academics and academic disciplines understand and approach internationalisation differently, as previous studies have shown. However, there is little research on the role of such disciplinary perspectives in relation to different internationalisation practices and interventions. Using the Becher-Biglan framework of academic tribes, this exploratory study compares 12 undergraduate programmes at a Dutch university of applied sciences and addresses the question if the different disciplinary approaches to internationalisation as identified in previous studies are also reflected in the choices of internationalisation at home activities. The findings show there is more variation in the range of activities rather than in the types of activities and that it is within the rationales underlying those choices where the influence of disciplinary perspectives is more visible.